A Analyze the Impact of Central Bank Regulatory Laws on Financial Inclusion in Iran's Usury-free Banking System - Hassan Mahdavi Panah; Maryam Khalili Araghi; Mehdi Montazer; Hamid Reza Vakilifard (تحقیقات مالی اسلامی (پیوسته))
One of the fundamental principles in the financial system for economic development and poverty reduction is financial inclusion, which is in line with the principles of justice and equality in the Islamic financial system. Financial inclusion refers to the accessibility, availability, and usage of the formal financial system by all members of an economy. Therefore, financial inclusion is a multi-dimensional phenomenon that requires effective supervision. Effective supervision not only strengthens the stability of banks but also ensures economic growth and builds trust in the financial system. One way to build trust is through the enactment and enforcement of laws that protect the interests of all stakeholders in a comprehensive economy. Therefore, the aim of this research was to present a model for analyzing the impact of central bank regulatory laws and financial technology on financial inclusion in the interest-free banking system in Iran. This study used a new approach to estimate the financial inclusion index. The research findings indicated that the regulatory laws of the central bank and financial technology are effective in developing financial inclusion. Furthermore, the research findings suggest that the development of financial technology, especially in the banking industry in recent years, has led to the expansion of financial inclusion in Iran, creating fair and equal access to financial products and services for individuals in society, which is the main goal of financial inclusion, and with the expansion of financial inclusion, financial deprivation in society has decreased.